Genome size and numerical polymorphism for the B chromosome in races of maize (Zea mays ssp. mays, Poaceae) - Rosato, M. (1998)
Twenty-one native populations (1120 individuals) of maize from Northern Argentina were studied. These populations, which belong to 13 native races were cultivated at different altitudes (80-3620 m). Nineteen of the populations analyzed showed B chromosome (Bs) numerical, polymorphism. The frequency of individuals with Bs varied from 0 to 94%. The number of Bs per plant varied from 0 to 8 Bs, with the predominant doses being 0, 1, 2, and 3. Those populations with varying number of Bs showed a positive and statistically significant correlation of mean number of Bs with altitude. The DNA content, in plants without Bs (A-DNA)(2n = 20), of 17 populations of the 21 studied was determined. A 36% variation (5.0-6.8 pg) in A-DNA content was found. A significant negative correlation between A-DNA content and altitude of cultivation and between A-DNA content and mean number of Bs was found. This indicates that there is a close interrelationship between the DNA content of A chromosomes and doses of Bs. These results suggest that there is a maximum limit to the mass of nuclear DNA so that Bs are tolerated as long as this maximum limit is not exceeded.